Analisis Kerangka Portal Keluli Secara Manual Dan Perisian S-Frame - Mohd Nazri, Fadzli (Universiti Sains Malaysia, 2005)
In design building process, the effect of wind load is less considered in design of low rise building. There are so many definitions of low rise building and normally categorized according to the height. For portal frame, regardless of its height, ( normally less than 15 m ) still need to be determined the wind load due to its big opening of the building. There are two types of standard code, that is wide used (BS 6399:Part 2: 1995) before the latest standard code of MS 1553:2002. In wind load calculation, Malaysian Standard (MS) that used is lower than the usage of British Standard, where 76% of differential in net wind pressure at the wall surface, and 94% of differential in roof surface. The main reasons are parameters used in MS is represent the true environment in Malaysia. In design portal frame,the safe size should be chosed because the size will influence the cost of material. Results shows that the cost from consultancy is 81% less by using the S-Frame software, compared to 64% of calculation manually. In terms of deflection in the x-axis, the design using the software S-Frame produces lower deflection at least 88% compared to the size proposed by consultancy, and 83% from the manual calculation. Normally, the effectivedesign will be produced by the experience engineer with the help of design software. This project also studies the potential replacement of universal column shaped H (UC) the universal I-beam shaped (UB) that is normally used in design of portal frame.